LEGAL PROTECTION AGAINST THIRD PARTIES IN GOOD FAITH IN THE PROCESS OF ASSET CONFISCATION OF CORRUPTION CRIMES (STUDY ON PT. ASABRI) - Emil Mursyidin Nasution; M. Citra Ramadhan; Rafiqi Rafiqi (SOSIOEDUKASI, 2025)
This study examines legal protection for good-faith third parties in the process of asset confiscation for corruption crimes, focusing on the case of PT. ASABRI. The main issues examined include: (1) what form of legal protection for good-faith third parties takes under the Indonesian legal system; (2) the legal obstacles faced by third parties in defending their rights to confiscated assets; and (3) the implementation of legal protection in the practice of asset confiscation in the PT. ASABRI corruption case. The type of research used is normative juridical, namely research that emphasizes literature studies through analysis of laws and regulations, legal doctrine, court decisions, and relevant legal literature. This study uses Gustav Radbruch's legal value approach, which includes justice, legal certainty, and utility as a normative analytical framework for legal protection. The nature of this research is descriptive and analytical, aiming to provide a comprehensive overview of legal regulations and their implementation in practice, as well as to analyze the effectiveness of legal protection for good-faith third parties. The research results indicate that although legal protection is normatively available, its implementation still faces various obstacles, such as overlapping criminal and civil law, and the lack of adequate defense mechanisms for third parties in asset confiscation proceedings.